Rural social enterprises as embedded intermediaries: The innovative power of connecting rural communities with supra-regional networks - Ralph Richter (Journal of Rural Studies, 2019)
The question of how social enterprises foster social innovation in rural regions remains largely unexplored. In this paper, I develop the assumption that the embeddedness of social enterprises in rural communities and their ability to connect rural communities with supra-regional networks and decision makers are crucial preconditions for generating and fostering social innovation in the countryside. By applying the social network approach and a cross-case analysis of social enterprises in rural regions of Austria and Poland, I show how rural social enterprises mobilise ideas, resources and support from external sources not primarily for their own benefit but for that of their rural region. As embedded intermediaries, they contribute to transformational change and wellbeing, albeit they are only one of many forces that drive rural development.
Keywords: 710; Rural social enterprises; Embedded intermediary; Social innovation; Social network analyses; Rural development